Bahasa Inggris Bahasa Inggris - Shevananda Arifianto; Ussy Andawayanti; Sumiadi (Jurnal Penelitian Pendidikan IPA, 2026)
Urban flooding is influenced by land use change, rainfall characteristics, river conveyance capacity, and downstream tidal conditions. This study evaluates the effect of land use conditions on hydrological response, flood inundation, and structural flood control performance using hydrological analysis and HEC-RAS modeling. The 2025 observed land use condition was classified using Landsat 9 imagery and supervised classification, while the 2031 scenario was based on the Semarang City Spatial Plan 2011–2031. The classification produced an overall accuracy of 85.42% with a Kappa coefficient of 0.83. The runoff coefficient increased from 0.41 in 2025 to 0.46 in 2031. The Nakayasu Synthetic Unit Hydrograph method estimated that the 25-year design flood discharge increased from 111.52 m³/s to 139.09 m³/s. HEC-RAS 1D/2D coupled unsteady flow simulation under the HWL condition showed that inundation increased from 12.21 ha to 17.24 ha. River normalization and levee construction improved channel conveyance capacity and reduced overflow potential in critical segments. These results indicate that integrating land use control and structural flood mitigation can support sustainable urban flood management.